Library users’ attitudes toward social media applications for dissemination of information in selected Nigerian university libraries (2019)
Social media is one of the most engaging communication tools of modern era. The use of the social media has permeated all aspect of human endeavour be it commerce, education, social, health and entertainment. Library as a social institution has adopted the use of the media to engage the clients and share information. However, the preliminary investigation conducted by the researcher indicated that the use of the media in the libraries has been confronted with different reactions among the clients. This study therefore explored users’ attitudes toward the use of social media applications for information dissemination in selected Nigerian university libraries (Kenneth Dike Library, University of Ibadan and Centre for Learning Resources, Covenant University). Descriptive statistics of frequency counts and percentages as well as inferential statistics of correlation method were used to analyse the study data. The results showed that the most prominent social media used for service delivery in the two university libraries are Facebook, WhatsApp, Flickr, Youtube and Instant Messaging. The findings indicated that significant number of respondents have positive disposition to the use of social media for information dissemination owing to the fact that the media offer immediate, relevant and better communication on library resources and services. The need to sustain the use of the social media for dissemination of information and possible filter of irrelevant contents from the media were recommended.